Creutzfeldt-Jakob Disease Presenting as Nonconvulsive Status Epilepticus - Aleksei Rakitin; Riina Vibo; Vaiko Veikat; Anne Õunapuu; Aive Liigant; Sulev Haldre (Case Reports in Neurological Medicine)
Creutzfeldt-Jakob disease is a rare, rapidly progressive spongiform encephalopathy in humans. EEG plays an important role in diagnosing this disease. In some patients, epileptic activity and encephalopathy from various aetiologies may share morphological features on EEG. This similarity could create difficulties in EEG interpretation, especially if the patient presents with disturbed consciousness. In this case report, a 74-year-old female with Creutzfeldt-Jakob disease presented initially with rapidly progressive impairment of consciousness and focal epileptiform activity on EEG. An EEG performed 25 days later showed periodic sharp-wave complexes with triphasic morphology at a rate of 0.5 Hz, compatible with a diagnosis of Creutzfeldt-Jakob disease. Based on these results, we recommend that a diagnosis of Creutzfeldt-Jakob disease be considered in patients presenting with a rapid deterioration of consciousness and a clinical presentation of nonconvulsive status epilepticus. Monitoring these patients with serial EEGs could be useful to establish an accurate diagnosis.